Efficient Quantum Circuits for Non-Qubit Quantum Error-Correcting Codes - Grassl, Markus; Roetteler, Martin; Beth, Thomas (International Journal of Foundations of Computer Science (IJFCS), 2002)
We present two methods for the construction of quantum circuits for quantum error-correcting codes (QECC). The underlying quantum systems are tensor products of subsystems (qudits) of equal dimension which is a prime power. For a QECC encoding k qudits into n qudits, the resulting quantum circuit has O(n(n-k)) gates. The running time of the classical algorithm to compute the quantum circuit is O(n(n-k)^2).